The Merck manual of diagnosis and therapy - Beers, Mark H.; Berkow, Robert (New Jersey : Merck Research Laboratories, 1999)
A compendium of facts and information on hundreds of diseases, including etiology, symptoms and signs, diagnosis and treatment.
1. Nutritional Disorders -- 2. Endocrine and Metabolic Disorders -- 3. Gastrointestinal Disorders -- 4. Hepatic and Biliary Disorders -- 5. Musculoskeletal Disorders -- 6. Pulmonary Disorders -- 7. Ear, Nose, and Throat Disorders -- 8. Ophthalmologic Disorders -- 9. Dental and Oral Disorders -- 10. Dermatologic Disorders -- 11. Hematology and Oncology -- 12. Immunology; Allergic Disorders -- 13. Infectious Diseases -- 14. Neurologic Disorders -- 15. Psychiatric Disorders -- 16. Cardiovascular Disorders -- 17. Genitourinary Disorders -- 18. Gynecology and Obstetrics -- 19. Pediatrics -- 20. Disorders Due to Physical Agents -- 21. Special Subjects -- 22. Clinical Pharmacology -- 23. Poisoning.
Includes index.
Keywords: THERAPEUTICS -- HANDBOOKS AND MANUALS